Kontrakt - Zanussi, Krzysztof (Poland, 1980)
The Contract is set during an "arranged" wedding ceremony. The bride and groom barely know each other, but this matters not at all to their tradition-bound families. At the last minute, the bride balks. Only slightly nonplussed, the groom's father, a status-seeking doctor, decides to go ahead with the expensive reception anyway.
Keywords: Fiction films